Occupational risk factors for prostate cancer in an area of former coal, iron, and steel industries in Germany. Part 2: results from a study performed in the 1990s. Issue 22 (1st December 2016) - Krech, Sabina; Selinski, Silvia; Bürger, Hannah; Hengstler, Jan G.; Jedrusik, Peter; Hodzic, Jasmin; Knopf, H.-Jürgen; Golka, Klaus
ABSTRACT: Currently, there is no established occupational risk factor for prostate cancer. However, in the 1980s, a hospital-based case-control study in the greater Dortmund area showed an elevated risk for hard coal miners and, based on few cases, for painters and varnishers. Therefore, approximately 10 yr later, a similar study regarding prostate cancer was performed in this area. In total, 292 patients with prostate cancer who underwent radical prostatectomy and 313 controls who underwent transurethral resection of a benign prostatic hyperplasia were investigated by questionnaire. All of them were operated on between 1995 and 1999. This study showed a decreased risk for prostate cancer in hard coal miners (odds ratio [OR] = 0.67, 95% confidence interval [CI] = 0.44–1.03). Occupational exposures related to an elevated risk for prostate cancer were exposures to combustion products (20% cases vs. 11% controls), colorants and dyes (19 vs. 13%), and cutting fluids (8 vs. 6%). The different prostate cancer risks for underground coal miners in two studies with a time interval of approximately 10 yr are striking. Factors to be discussed are the introduction of prostate-specific antigen (PSA) screening for prostate cancer and investigation of cases that underwent radical prostatectomy, where the disease in general is locally confined. Working conditions in the local underground coal mines improved over time but did not change markedly in the period of interest. In essence, the present study does not corroborate an elevated prostate cancer risk in former underground hard coal miners from the greater Dortmund area.